Narradores-trapeiros, anarquivamento e fragmentação em romances de Benedicto Monteiro - Pacheco de Souza, Abílio (E-Letras com vida, 2022)
The novels by Benedicto Monteiro Verde vagomundo (1972), O minosauro (1975) and A terceira margem (1983), written and published in the context of the Brazilian military dictatorship, employ in their compositions the technique of montage and fragmentation, common to other novels from the 1970’s (Franco, 1998), and they appear to us in their non-conforming feature as disjointed fractals and as self-moving trees (Pacheco, 2020). Mobilizing diverse discursive materials collected in society and inserting them in the novel, the narrator promotes a disorder in the logic of the Western, Cartesian, Enlightenment archive, he acts like a garbage collector, like the Baudelairean ragpicker, to put us in front of an anti-archive. He collects and presents the reader with a seemingly random collection of radio transcripts, newspaper and magazine news, songs lyrics, poems, technical reports, testimonials, and other discursive material. In this paper, we analyze the rag-picker narrator and the anarchivation, the anarchivation of the archive that shakes the edifice of Western reason, as the residues of society are collected from the ruins to critically reconstruct a discourse (according to Seligmann-Silva, 2014). Anarchivation, as a gesture of disorder and fragmentation, carried out by the narrators, appears as an aesthetic principle and corresponds to the perception of shock by the subject in the face of the rigging of the State and the vertigo caused by the violent, technocratic apparatus. After all, in the context in which the novels were written, the measure of good and evil and the subjugation of the subject's autonomy are under the rule of a State whose policy is based on violence and control (Todorov, 2008). Fragmentation and anarchivation as ways of disposing the narrative correspond to the way of perceiving himself, others and the world by this narrator, also disjointed, in a context and because of a violent, adverse, degrading context.